MODULASI DALAM PENERJEMAHAN KALIMAT MAJEMUK BERTINGKAT BAHASA INGGRIS KE BAHASA INDONESIA PADA NOVEL THIRD GIRL - Terweline Tapilatu (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
Translating a text from English into Indonesian requires specific procedures to ensure meaning equivalence between the source and target texts. One such procedure is modulation or a shift in perspective. This descriptive research, which uses the content analysis method, illustrates the use of modulation in translating English complex sentences into Indonesian sentences found in Agatha Christie’s novel Third Girl and its Indonesian translation. The objectives are to gain a deep understanding of the modulation subtypes used and their impact on meaning equivalence. The findings revealed that the translator mainly used obligatory modulation (61%) rather than free modulation (39%). Obligatory modulation includes subtypes such as reversal of terms, particular for general and vice versa, explicative modulation, passive for active, negation of opposite, and part for whole. Free modulation includes concrete for abstract, effect for cause, negation of opposite, change of symbols, and exchange of intervals for limits (time). The use of these subtypes results in changes in tone, nuance, the focus of meaning, meaning reduction, meaning addition, and cultural adaptation. These changes support meaning equivalence by producing a translation that is idiomatic, natural, acceptable, and culturally appropriate in the target language.